Web-Based ERP System Prototype for Enhanced Inventory and Supply Chain Management in the Logistics Industry - Hadikin, Valdy Beniah; Wiratama, Jansen (ULTIMA InfoSys, 2024)
Technological advancements have driven companies to adopt innovative solutions to improve efficiency and streamline operations. PT Kesuma Express, a logistics company in Indonesia, faced inefficiencies and frequent errors due to its reliance on manual processes such as transaction recording, document management, and income reporting. This research developed a web-based Enterprise Resource Planning (ERP) system prototype to address these challenges, focusing on Inventory and Supply Chain Management (SCM) modules. The prototype uses the Rapid Application Development (RAD) model and the Laravel framework and includes key features such as transaction recording, customer data management, and financial reporting. The inventory module enhances truck data management, monitors truck availability, and alerts users about data discrepancies, ensuring accuracy and timely actions. The SCM module supports the delivery process by providing real-time delivery status tracking that is accessible to both warehouse staff and administrators, enabling transparency and efficiency in goods distribution. The system replaced PT Kesuma Express manual processes, significantly improving operational efficiency and reducing errors. By integrating inventory and SCM capabilities, the ERP system has streamlined operations, enhanced data accuracy, and improved customer service quality. This research demonstrates the transformative potential of ERP systems for logistics companies aiming to modernize their operations.